2021
DOI: 10.3390/ijerph182412922
|View full text |Cite
|
Sign up to set email alerts
|

Stress and Adjustment during the COVID-19 Pandemic: A Qualitative Study on the Lived Experience of Canadian Older Adults

Abstract: In response to the COVID-19 pandemic, social distancing measures were put into place to flatten the pandemic curve. It was projected that older adults were at increased risk for poor psychological and health outcomes resulting from increased social isolation and loneliness. However, little research has supported this projection among community-dwelling older adults. While a growing body of research has examined the impact of the COVID-19 pandemic on older adults, there is a paucity of qualitative research that… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
36
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 24 publications
(41 citation statements)
references
References 38 publications
4
36
0
1
Order By: Relevance
“…As found in prior studies, participants in this study adjusted their routines during the COVID-19 pandemic to engage in activities that were meaningful to them ( Huntley & Bratt, 2022 ), that supported their mental and physical health, such as exercise ( Ejiri et al, 2021 ; Takashima, Onishi & Hirano, 2020 ; Whitehead & Torossian, 2021 ), shaping their trajectories during the pandemic. Similar to prior studies during the COVID-19 pandemic, participants described their enhanced enjoyment of daily activities ( Fiocco et al, 2021 ; Huntley & Bratt, 2022 ). Older adults also employed strategies to facilitate high-quality interactions, including doing shared activities or using humour, which improves social connectedness and is associated with better health ( Fingerman et al, 2021 ; Rossignac-Milon & Higgins, 2018 ; Zhaoayang et al, 2019 ).…”
Section: Discussionmentioning
confidence: 62%
See 4 more Smart Citations
“…As found in prior studies, participants in this study adjusted their routines during the COVID-19 pandemic to engage in activities that were meaningful to them ( Huntley & Bratt, 2022 ), that supported their mental and physical health, such as exercise ( Ejiri et al, 2021 ; Takashima, Onishi & Hirano, 2020 ; Whitehead & Torossian, 2021 ), shaping their trajectories during the pandemic. Similar to prior studies during the COVID-19 pandemic, participants described their enhanced enjoyment of daily activities ( Fiocco et al, 2021 ; Huntley & Bratt, 2022 ). Older adults also employed strategies to facilitate high-quality interactions, including doing shared activities or using humour, which improves social connectedness and is associated with better health ( Fingerman et al, 2021 ; Rossignac-Milon & Higgins, 2018 ; Zhaoayang et al, 2019 ).…”
Section: Discussionmentioning
confidence: 62%
“…Older adults in our study felt the longevity of pandemic restrictions contributed to declines in their health and well-being, supporting studies suggesting that reductions in social interactions and exercise were associated with declines in cognitive function and well-being during the COVID-19 pandemic ( De Pue et al, 2021 ; Noguchi et al, 2021 ). One barrier to older adults’ engagement in essential activities for health and wellness is that they felt uncomfortable using community spaces due to fear that the public would not abide by pandemic measures, such as social distancing, as found in prior studies ( Brooke & Clark, 2020 ; Fiocco et al, 2021 ). In our study, participants revealed that when preventative measures were suggestions rather than regulations, such as those pertaining to wearing a mask indoors at some points during the study period, this discomfort was exacerbated and resulted in them avoiding those community spaces.…”
Section: Discussionmentioning
confidence: 97%
See 3 more Smart Citations